A phytoplankton time series in the Northwestern Adriatic Sea: Structure and dynamics of the assemblages in a coastal ecosystem. (5th November 2022) - Casabianca, Silvia; Capellacci, Samuela; Ricci, Fabio; Scardi, Michele; Penna, Antonella
Abstract: Phytoplankton assemblage structure was analyzed based on time series data (2008–2019) together with environmental variables in two coastal sites in the Northwestern Adriatic Sea. The main component of phytoplankton assemblage was the diatom group. Distinct seasonal and inter annual variations in the presence of taxa were observed within the phytoplankton assemblage over the study period. Mainly four taxa showed a non-random pattern in the binary time series, such as three diatoms Skeletonema marinoi, Thalassionema nitzschioides and Dactyliosolen fragilissimus, and undetermined Dinophyceae. S. marinoi was more frequent in winter and early spring, whereas T. nitzschioides showed an opposite pattern, being more frequent in late spring and summer. In both cases, deviation from randomness was caused by a clear and almost stationary annual cycle. On the contrary, deviation from randomness depended on the long-term trend of D. fragilissimus time series, as this diatom showed an increasing frequency of occurrence since 2016. A clear phytoplankton assemblage structure affected by seasonal and environmental factors was observed. This was very evident for representative specie (i.e., S. marinoi associated with colder and rich nutrient waters or Heterocapsa niei and T. nitzschioides associated with high temperature and low nutrient conditions) and other species associated with various environmental parameters. Furthermore, the analysis of the association among phytoplankton taxa showed a partial and varied pattern. Our results highlight that phytoplankton time series showed changes in assemblage structure exhibiting a regular 12-month period affected by environmental factors. The long time series observations are important to understand the phytoplankton assemblage structure in relation to environmental changes and human pressures, crucial to achieving the Good Environmental Status in compliance to environmental directives. Highlights: Long-term changes of phytoplankton assemblage were mainly driven by environmental variables. Usefulness of time series data for describing phytoplankton assemblage structure. A regular periodic pattern of phytoplankton assemblages in NW Adriatic Sea was observed. Diatoms as the main group component of the NW Adriatic phytoplankton assemblages.